Political Will of the Head of Badan Pertanahan Nasional Bogor Regency I against Land Mafia Cases through the Implementation of Electronic Certificates - Darmawan, Eka Krisna Cahya; Ridwan, Ridwan (Journal La Sociale, 2025)
The land mafia issue in Indonesia, including in Bogor Regency, threatens agrarian justice and legal certainty over land ownership. Weak transparency and accountability in the land system, along with the involvement of unscrupulous BPN officials, worsen the situation. This study analyzes the political will of the Head of the National Land Agency (BPN) of Bogor District I in addressing land mafia cases through the implementation of electronic land certificates. Using a qualitative approach, data were collected through documentation and in-depth interviews. The study applies Brinkerhoff's political will framework, which includes indicators of public commitment, resource mobilization, policy consistency, and stakeholder engagement. Findings reveal that the success of electronic certificates is strongly influenced by the leadership and commitment of the Head of BPN Bogor I in supporting land digitization as a systemic measure against land mafia practices. Beyond technological innovation, electronic certificates serve as a local strategy for agrarian reform and legal enforcement. This research recommends strengthening institutional synergy, improving public digital literacy, and ensuring transparency in land certificate issuance to support sustainable land governance.